The role of sports diplomacy in the sociology of international relations: A case study of the BRICS countries - Ramazan, Ainur; Salikzhanov, Rinat; Aktayev, Serik; Baitassov, Yesset; Shoqparov, Alibek (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the role of sports diplomacy in enhancing international relations and promoting social integration, focusing on how mega-sporting events strengthen diplomatic ties. It explores sports as a “soft power” tool, with particular attention to its social, cultural, and economic impacts in BRICS countries (Brazil, Russia, India, China, and South Africa). The research employs a combination of data collection and correlational analysis, using data from major sporting events such as the Olympics, FIFA World Cups, and BRICS Games. It investigates the social, cultural, and political effects of these events, with a special focus on BRICS nations. The analysis reveals significant correlations: a positive correlation (r = 0.76) between public participation and sports involvement, a strong correlation (r = 0.85) between Olympic participation and infrastructure development, and a high correlation (r = 0.88) between social inclusion and government policies. These findings highlight the role of sports diplomacy in promoting public engagement, social equity, and infrastructure development. Sports diplomacy, as a form of soft power, plays a key role in advancing international relations, fostering social inclusion, and driving economic growth. The findings offer practical insights for policymakers, particularly in BRICS countries, on strategically utilizing sports diplomacy to enhance foreign policy and build global partnerships.